2014
DOI: 10.18632/oncotarget.2280
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast-derived WISP-1 increases VCAM-1 expression and enhances prostate cancer metastasis by down-regulating miR-126

Abstract: Bone metastases of prostate cancer (PCa) may cause intractable pain. Wnt-induced secreted protein-1 (WISP-1) belongs to the CCN family (CTGF/CYR61/NOV) that plays a key role in bone formation. We found that osteoblast-conditioned medium (OBCM) stimulates migration and vascular cell adhesion molecule-1 (VCAM-1) expression in human PCa (PC3 and DU145) cells. Osteoblast transfection with WISP-1 shRNA reduced OBCM-mediated PCa migration and VCAM-1 expression. Stimulation of PCa with OBCM or WISP-1 elevated focal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…As with Wnt2, WISP-1 has been studied in cancer cells, where it has been shown to be a chemoattractant, 20 encourage metastasis, 29 increase invasiveness, and decrease chances of survival. [30][31][32] WISP-1 has also been shown in human cancer cells to be upregulated compared with healthy cells 33 and to stimulate migration via NFκB activation of MMP-2.…”
Section: Arterioscler Thromb Vasc Biolmentioning
confidence: 99%
“…As with Wnt2, WISP-1 has been studied in cancer cells, where it has been shown to be a chemoattractant, 20 encourage metastasis, 29 increase invasiveness, and decrease chances of survival. [30][31][32] WISP-1 has also been shown in human cancer cells to be upregulated compared with healthy cells 33 and to stimulate migration via NFκB activation of MMP-2.…”
Section: Arterioscler Thromb Vasc Biolmentioning
confidence: 99%
“…Cells were seeded on six-well plates, then transiently transfected with VEGF-C 3 -UTR luciferase plasmids using Lipofectamine 2000 as described previously [37]. Cells collected were lysed with reporter lysis buffer 24 h after transfection, and the luciferase and Renilla activities in the cellular extracts were determined by the dual-luciferase reporter assay kit.…”
Section: Luciferase Reporter Assaymentioning
confidence: 99%
“…For example, miRNA (miR)-126, originally identified as an endothelial-specific miRNA playing an essential role in angiogenesis and vascular integrity, [9][10][11] has been shown to function as a critical tumor suppressor in various types of solid tumors. 5,[12][13][14][15][16][17][18][19] In contrast, we have shown that miR-126 is aberrantly overexpressed and likely plays an oncogenic role in core binding factor (CBF) leukemia. 20 CBF leukemia is characterized by the presence of a t(8;21)(q22;q22) or an inv(16)(p13.1q22) chromosomal rearrangement, which accounts for ;20% to 30% of primary acute myeloid leukemia (AML) cases.…”
mentioning
confidence: 99%